Reviving Perennial Wisdom: Seyyed Hossein Nasr’s Model as A Solution to Modern Crises - Manna, Nur (Islamic Thought Review, 2024)
This article presents a comprehensive examination of Seyyed Hossein Nasr's evaluation model within the context of perennial philosophy. Nasr’s model advocates for the revival of perennial wisdom—a traditional Islamic perspective that he believes offers a remedy to the contemporary crises plaguing modern civilization. According to Nasr, both Western and Islamic civilizations have faltered in achieving their fundamental objectives, leading to deteriorating human relations and widespread spiritual disillusionment, which in turn adversely impacts the environment. This paper employs a library research methodology, synthesizing data from a variety of sources including books, academic journals, and other relevant media. Through the lens of Nasr’s concepts, the study explores how his ideas might serve as a conduit for re-aligning contemporary society with the core principles of Islam and addressing the spiritual and existential challenges of modernity. Additionally, the paper discusses the potential reapplication of Sufism as a strategic approach to mitigate the crisis induced by rapid technological advancements and societal changes. By reintroducing and integrating these traditional insights, the study aims to offer solutions to the multifaceted problems faced by contemporary human societies.